Response of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage - D. W. Sweeney; Philip Barnes; Gary Pierzynski (Kansas Agricultural Experiment Station Research Reports, 2016)
(Abstract only. Link to: http://newprairiepress.org/kaesrr/vol1/iss4/3/) Article is nearly identical toResponse of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage, previously published in Southeast Agricultural Research Center Reports 2015. The residual effects of turkey litter and fertilizer amendments applied in previous years had little effect on the yield, yield components, and dry matter production of the following soybean crop grown in 2014.
Keywords: Soybean; Claypan; Turkey litter; Tillage